Effect of slag adjustment on inclusions in Si–Mn-killed steel during ladle furnace (LF) refining process. (14th September 2021) - Liu, Zonghui; Song, Guodong; Deng, Zhiyin; Zhu, Miaoyong
ABSTRACT: In the present study, some steel and slag samples were taken in industry to investigate the effect of slag adjustment on the inclusions in tyre cord steel. The disadvantage of slag adjustment process was discussed in contrast to the process with low basicity slag. The results show that the overall evolution routes of inclusions are the same in both processes with and without slag adjustment. The inclusions transform from MnO–SiO2 inclusions to CaO–MnO–SiO2 system inclusions, and even CaO–SiO2 system inclusions during LF refining process. The adjustment of slag influences the dissolved oxygen in liquid steel evidently, thus impacts the dissolved elements e.g. Ca, Mg, and Al in liquid steel, and the evolution of inclusions. The composition fluctuations of the inclusions caused by slag adjustment increase the risk of non-deformable inclusions. Low slag basicity during the whole refining process is strongly recommended.